Biografien bedeutender österreichischer Wissenschafterinnen "Die Neugier treibt mich, Fragen zu stellen" - Korotin, Ilse (2018)
This volume follows the results of the dictionary  "Wissenschafterinnen in und aus Österreich. Leben - Werk - Wirken" from 2002, in which the field of activities of the first generation of female scientists at austrian universities and in non-university workplaces were researched among other things. The present collection is now mostly focused on woman-specific acting of female scientists after 1945 (years of birth between 1930 and 1950, including an addition of earlier years). The emphasis in terms of time furthermore includes theoretical and personnel effects of the second feminist movement, developed in universities in the 1970s out of woman-specific problems in the fields of science.